Capillary assemblies in a rotating magnetic field. Issue 44 (29th October 2019) - Grosjean, Galien; Hubert, Maxime; Collard, Ylona; Sukhov, Alexander; Harting, Jens; Smith, Ana-Sunčana; Vandewalle, Nicolas
Abstract : The rotational dynamics of magnetocapillary assemblies is studied, aiming to design and understand self-assembled microswimmers and micromixers. Abstract : Small objects floating on a fluid have a tendency to aggregate due to capillary forces. This effect has been used, with the help of a magnetic induction field, to assemble submillimeter metallic spheres into a variety of structures, whose shape and size can be tuned. Under time-varying fields, these assemblies can propel themselves due to a breaking of time reversal symmetry in their adopted shapes. In this article, we study the influence of an in-plane rotation of the magnetic field on these structures. Various rotational modes have been observed with different underlying mechanisms. The magnetic properties of the particles cause them to rotate individually. Dipole–dipole interactions in the assembly can cause the whole structure to align with the field. Finally, non-reciprocal deformations can power the rotation of the assembly. Symmetry plays an important role in the dynamics, as well as the frequency and amplitude of the applied field. Understanding the interplay of these effects is essential, both to explain previous observations and to develop new functions for these assemblies.